1998
DOI: 10.1203/00006450-199807000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Lung mRNA Levels of Hox Genes Are Differentially Altered by Maternal Diabetes and Butyrate in Rats

Abstract: Diabetes is known to be associated with delayed lung development in humans and in experimental animals. This includes delayed expression of surfactant apoproteins. An important component of the metabolic abnormalities in diabetes is elevated levels of analogs of butyric acid, and the effects of diabetes on surfactant apoproteins can be reproduced by exposure of fetal rat lung explants to butyrate. Dexamethasone has the opposite effects on lung development. In humans, antenatal exposure to dexamethasone results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…In conclusion, we demonstrated that Hox genes are expressed in a region‐specific manner along the adult GI tract. Considering the critical role of Hox genes in morphogenesis and their abnormal expression pattern after various teratogen exposures (Jacobs et al . 1998; Li et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, we demonstrated that Hox genes are expressed in a region‐specific manner along the adult GI tract. Considering the critical role of Hox genes in morphogenesis and their abnormal expression pattern after various teratogen exposures (Jacobs et al . 1998; Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Li & Shiota 1999) showed that heat treatment induced embryonic day‐specific vertebral transformations accompanied by altered expression of Hox genes. Jacobs et al . (1998) demonstrated abnormal Hox expression in the lungs of fetuses from streptozotocin‐treated rats.…”
Section: Introductionmentioning
confidence: 99%
“…30 Although the link between homeobox genes and diabetes-induced CRS has not yet been reported in the literature, maternal diabetes has been shown to alter expression of Hox genes in fetal rat lungs. 31 The teratogenic insult in diabetic embryopathy occurs from the third to seventh week of gestation at the initiation of organogenesis. 32 In rats, uncontrolled diabetes produced lumbosacral malformations only during the period of organ differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Rats fetuses, with streptozoticin-induced diabetes, display altered Hox gene expression in the lung. This effect is mediated by butyrate and reversed by dexamethasone (Jacobs et al, 1998).…”
Section: Homeobox Genes Diseases and Metabolic Alterationsmentioning
confidence: 91%